Prevalence and identification of irregular erythrocyte antibodies in voluntary blood donors in the territory of Southeast Serbia - Randjelović, Milica; Veličković, Ana; Vojinović, Jelena; Stanojković, Zoran (Vojnosanitetski pregled, 2024)
Background/Aim. The purpose of tests for transmittable diseases, as well as determining ABO group, Rh typing, and the presence of clinically significant erythrocyte antibodies, is to enable the appropriate selection of blood/blood components for transfusion, to prevent or minimize adverse effects of transfusion, and to identify donors whose units of blood/components are not suitable for transfusion. The aim of the study was to evaluate the presence of irregular erythrocyte antibodies as well as to determine the specificity and origin of these antibodies in voluntary donors. Methods. This prospective observational study, conducted from January until July 2023, included samples of voluntary blood donors (BDs) for antibody screening in the population of voluntary BDs in the territory of Southeast Serbia. A total of 23,082 samples from healthy BD were examined through this period. Results. The overall prevalence of irregular anti-erythrocyte antibodies was 0.1125%, with anti-K, anti-D, and anti-E being the most frequently identified alloantibodies. Out of a total of 26 donors with positive screening results, 11 (42.32%) had alloantibodies, and 15 (57.68%) had antibodies of undetermined specificity. A positive antibody test was observed more frequently in male donors, and the age range of 51 years and above accounted for the majority of positive cases. Conclusion. Immunohematological testing, including antibody screening in voluntary BDs, is important for safe blood transfusion and is of great clinical importance. Likewise, it reduces the risk of complications due to incompatible transfusions.
Keywords: abo blood-group system; antibodies; blood donors; serbia